Hubungan Peran Orang Tua dengan kelengkapan Imunisasi Pada Balita di Kelurahan Buraen Kecamatan Amarasi Selatan - Lagut, Yosefina Frisnarati Novita; S. Tusi, Juandri; Rihi, Priyati; H. Pella, Yosin; R. Pandie, Fance (NHM PRESS, 2024)
Immunization is a government initiative aimed at preventing individuals from contracting certain diseases by boosting the body's immunity. The immune systems of babies and toddlers (children under the age of five) are not as fully developed as those of adults, making them more vulnerable to certain diseases. This study aims to determine the relationship between the role of parents and the completeness of immunization for toddlers in Buraen Village, South Amarasi District. This research employs a descriptive, non-experimental correlation design using cross-sectional methods. The sampling technique used in this study was random sampling, with a total sample size of 103 parents and children under 5 years old in Buraen Village, South Amarasi District. Based on the research results, it was found that out of the 103 toddlers, 90 received complete immunization and their parents agreed that their involvement was influential. Conversely, for the 13 toddlers who did not receive complete immunization, their parents disagreed about the influence of their role. The chi-square test results indicated a p-value of 0.002, which is less than 0.05. This signifies a significant relationship between the role of parents and the success of immunization in Buraen Village